Design and synthesis of novel schiff base-benzothiazole hybrids as potential epidermal growth factor receptor (EGFR) inhibitors - Singh M.; Singh S.K.; Thakur B.; Ray P.; Singh S.K. (My University, 2025)
A series of novel Schiff bases -benzothiazole hybrids was designed, synthesized and evaluated for their anticancer activity by MTT assay and western blot method. Antiproliferative screening indicated that compound containing dihydroxy substituents had potent inhibitory activity with IC50 value 34μg/ml against SKOV3, A2780-S and A2780-CR cell lines. It showed more potent cytotoxicity in combination with cisplatin and paclitaxel than alone in the selected cell lines (SKOV3, A2780 and A2780-CR models). The in vitro cytotoxicity of the compounds on IOSE 364 cell line was evaluated to establish the selectivity. Molecular docking study exhibited good binding against epidermal growth factor receptor, which was further ascertained by immunoblot assay using specific antibody against phosphorylated EGFR, and thus unravelling the targeted anticancer mechanism. © 2016 Bentham Science Publishers.